Perencanaan Jadwal dan Rute Distribusi Rokok Untuk Menekan Total Biaya Transportasi - Thomy Eko Saputro; Aprilia Prihatina (Jurnal Teknik Industri, 2012)
One of the main issue in improving the customer service is how to deliver the product on time to customers. Therefore, the stakeholders need to apply an appropriate strategy in order to make distribustion process become more efficient and effective. Because it is hard to determine appropriate schedule and route when dealing with a lot agents, PR 567 as a representative distributor of cigarette in Purwodadi attempts to make its distribution process better. This was done by using PVRP (Periodic Vehicle Routing Problem) model with cluster first-second route approach and optimization method for assigning vehicle. The result of this research were frequency, schedule, and route with the most minimum transportation cost. In this research, the distribution area was defined into two cluster. The best delivery frequency for cluster one was once week, while cluster two was three times a week. The transportation cost was Rp725805/week. In the other hand, the saving cost was Rp320189/week or 44%/week from the initial cost.